RETHINGKING MARKETING MADRASAH Menimbang Pola dan Strategi Pemasaran Jasa Pendidikan Madrasah - Imam Machali Machali (Badan Litbang dan Diklat Kementerian Agama RI, 2015)
AbstractSince the 1980’s Islamic educational institutions in Indonesia have been varied in types. At first mainstream Islamic educational institutions included school, madrasah and Islamic schools but in the last two decades new model of variant have been coming out in the forms of Integrated Islamic School (SIT), Islamic School with International Perspective (SIBI), International Islamic School (Intis School), and others with numerous variants and affiliates. This becomes an interesting phenomenon and at the same time constitutes a challenge and competitor for mainstream Islamic institutions such as madrasahs. This article describes the development of variants and new trend of Islamic educational institutions in Indonesia and offers strategies and innovation in the development of madrasah in the perspective of educational service marketing management through the strategy of rethinking madrasah marketing strategy. Abstrak Sejak tahun 1980-an lembaga pendidikan Islam di Indonesia mengalami perkembangan variasi. Pada mulanya mainstream lembaga pendidikan Islam adalah sekolah, madrasah dan sekolah Islam. Maka pada dua dekade terakhir ini Muncul varian baru model Pendidikan Islam berbentuk Sekolah Islam Terpadu (SIT), Sekolah Islam Berwawasan Internasional (SIBI), International Islamic School (Intis School), dan lain-lain dengan berbagai varian dan afiliasinya. Hal ini menjadi fenomena menarik dan sekaligus menjadi tantangan dan kompetitor bagi lembaga pendidikan Islam mainstream seperti madrasah. Artikel ini mendeskripsikan perkembangan varian dan trend baru lembaga pendidikan Islam di Indonesia dan menawarkan strategi dan inovasi pengembangan madrasah dalam perspektif manajemen pemasaran jasa pendidikan melalui strategi rethingking marketing madrasah.